2019
DOI: 10.1590/1983-21252019v32n108rc
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Phosphorus Doses on Coffee Growth Under a Non-Sterile Soil

Abstract: The use of mycorrhiza is a promising biotechnology that makes coffee cultivation sustainable in the use of fertilizers. In this sense, plant growth and phosphorus contents were assessed in coffee inoculated with Rhizophagus clarus, Claroideoglomus etunicatum and Dentiscutata heterogama in soil fertilized with 0, 0.74, 1.48 and 2.96 g P2O5 kg-1. The experimental design was a randomized block design in a 4 × 4 factorial scheme with four replications. The mycorrhizal seedlings were previously produced and later t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
2
6
0
2
Order By: Relevance
“…The results of this study indicate that the species of inoculated AMF affects the response of the plant, corroborating with other studies with AMF in symbiosis with plants (Saggin-Júnior et al, 1995;Moreira et al, 2019).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study indicate that the species of inoculated AMF affects the response of the plant, corroborating with other studies with AMF in symbiosis with plants (Saggin-Júnior et al, 1995;Moreira et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…Another important point to be explored is how the species and genes of AMF used in the controlled inoculation. Moreira et al (2019) studied Gigaspora margarita and Rhizophagus clarus and observed an increase to shoot dry mass and root system when compared with the noninoculated treatment. Therefore, the species of AMF affect positively the answer of the plant and present a positive point regarding programs of controlled use of AMF.…”
Section: Resultsmentioning
confidence: 99%
“…A colonização radicular por hifas não ultrapassou 10% e as menores taxas ocorreram no RUC 37H, apesar do solo dessa clareira apresentar o menor teor de P, fator determinante para que houvesse a maior colonização de hifas das espécies vegetais, tendo em vista que esse nutriente interfere negativamente na colonização radicular por fungos micorrízicos arbusculares (SMITH et al, 2010;MOREIRA et al, 2019).…”
Section: Resultsunclassified
“…Nogeira -Cardoso, 2000;Stürmer & Siqueira, 2006;França, de Freitas, dos Santos, Grazziotti, Andrade, 2016;Cogo et al, 2017;Moreira, França, Grazziotti, Leal, & Silva, 2019), México con 15 (Trejo-Aguilar et al, 2011;Arias et al, 2012;Posada et al, 2012;Pérez-Luna, Álvarez-Solís, Hernández-Cuevas, & Sánchez-Roque, 2016;Posada, Sánchez, Heredia-Abarca, & Sieverding, 2018;Herrera-Monroy, Castro-Brindis, Pérez-Moreno, & Valdés-Velarde, 2019;Bertolini, Montaño, Salazar, Chimal, & Varela, 2020) y Colombia con 33 (Posada et al, 2012;Posada et al, 2018), además de ser los países con más trabajos publicados. En Perú hay 10 reportes (Vallejos-Torres, Arévalo, Iliquin, & Solís, 2019), en Cuba 9 (Sánchez et al, 2000) y en Puerto Rico, 2 (Lebrón, Lodge, & Bayman, 2012).…”
Section: Especies De Hma En América Latinaunclassified